Aportaciones al estudio de la alianza Trachynion distachyae Rivas-Martínez 1978 en el sector Subbético (Andalucía-España) - Torres, Juan Antonio; García-Fuentes, Antonio; Salazar, Carlos; Cano, Eusebio (Lazaroa, 2000)
Torres, J. A., García-Fuentes, A., Salazar, C. & Cano, E. Contribution to the study of the alliance Trachynion distachyae Rivas-Martínez 1978 in the Subbaetic sector (Andalusia, Spain). Lazaroa 21: 19-23 (2001). We have carried out a study on short pioneer xerophilous therophytic grasslands that colonise calcareous, non-nitrified soils that are poor in organic matter in the Subbaetic sector (Baetic subprovince); they belong to the phytosociological alliance Trachynion dystachiae. We propose a new association for the oro-Mediterranean thermotype (Jonopsidio prolongoi-Hornungietum petraeae) by providing information about its structure, synecology, synchorology, syntaxonomy and dynamics. bético-Maginense (TORRES, 1997), donde constituye